2022
DOI: 10.1039/d2ta00323f
|View full text |Cite|
|
Sign up to set email alerts
|

Study of thermal material properties for Ta- and Al-substituted Li7La3Zr2O12 (LLZO) solid-state electrolyte in dependency of temperature and grain size

Abstract: Solid-state electrolytes such as tantalum (Ta)- and aluminum (Al)-substituted Li7La3Zr2O12 (LLZO) are seen as the key component for the next generation of mainstream battery technology. However, this development often lacks...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 81 publications
2
8
0
Order By: Relevance
“…Since the discovery of Li 7 La 3 Zr 2 O 12 (LLZO) solid‐state electrolytes (SSEs) and the realization of their high potential to replace combustible organic electrolytes in Li‐ion batteries [ 1–5 ] and enable the use of Li metal anodes, [ 6–10 ] the research on Li/LLZO interface [ 11–16 ] and the compatibility of LLZO with current cathode chemistries [ 17–21 ] has progressed at an impressive pace. However, despite these stunning recent developments, the electrochemical performance and energy density of batteries based on LLZO SSE are far below the required levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of Li 7 La 3 Zr 2 O 12 (LLZO) solid‐state electrolytes (SSEs) and the realization of their high potential to replace combustible organic electrolytes in Li‐ion batteries [ 1–5 ] and enable the use of Li metal anodes, [ 6–10 ] the research on Li/LLZO interface [ 11–16 ] and the compatibility of LLZO with current cathode chemistries [ 17–21 ] has progressed at an impressive pace. However, despite these stunning recent developments, the electrochemical performance and energy density of batteries based on LLZO SSE are far below the required levels.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of Li 7 La 3 Zr 2 O 12 (LLZO) solid-state electrolytes (SSEs) and the realization of their high potential to replace combustible organic electrolytes in Li-ion batteries [1][2][3][4][5] and voids. [30][31][32][33][34][35] On the one hand, the formation of voids during stripping can be mitigated by the larger surface area of the LLZO/Li interface in the scaffold compared to dense LLZO ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the corresponding Raman spectrum exhibits major Raman modes at 309 cm −1 , which can be related to the La 2 Zr 2 O 7 impurity phase. 36,37 This indicates that excessive sintering induces phase transformation from the cubic into the tetragonal phase. 27 Furthermore, the higher the sintering temperature, the broader the peak corresponding to the intermediate energy region 200-500 cm −1 of the vibrational mode of the Li-O bond.…”
Section: Resultsmentioning
confidence: 99%
“…It was subsequently shown that significant portions of heat are conducted by so-called diffusons (nonplane-wave phonons) that exchange thermal energy in a random-walk fashion with other diffuson-type phonons . Recently, this type of thermal transport was found to contribute in structurally complex or anharmonic materials as well, and given the glass-like thermal conductivity of Li 6 PS 5 Cl and other lithium solid electrolytes reported by Cheng et al, Neises et al, and Bock et al, it is likely that diffusons contribute to thermal transport in these material classes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that thermal conductivities of most solid electrolytes, both sulfide , and oxide-based , , have low thermal conductivities (0.5 to 1.5 W m –1 K –1 ) comparable to liquid carbonate-based electrolytes (0.6 W m –1 K –1 ) used in conventional systems. Consequently, thermal management challenges in Li-ion batteries that originate from poor heat dissipation (depending on the thermal conductivity) can be expected in solid-state systems as well .…”
Section: Introductionmentioning
confidence: 99%